2019
DOI: 10.1002/cne.24643
|View full text |Cite
|
Sign up to set email alerts
|

A model of neocortical area patterning in the lissencephalic mouse may hold for larger gyrencephalic brains

Abstract: In the mouse, two telencephalic signaling centers orchestrate embryonic patterning of the cerebral cortex. From the rostral patterning center in the telencephalon, the Fibroblast Growth Factor, FGF8, disperses as a morphogen to establish the rostral to caudal axis of the neocortical area map.FGF8 coordinates with Wnt3a from the cortical hem to regulate graded expression of transcription factors that position neocortical areas, and control hippocampal development. Whether similar signaling centers pattern the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 89 publications
(123 reference statements)
0
7
0
Order By: Relevance
“…In mice, this pathway operates to prevent differential expansion of cortical progenitors and suppress gyrification of the distant neocortex. It has been recently demonstrated that similar to the mouse, a Wnt3a-expressing signaling center is also present in the DMe of the naturally gyrencephalic ferret 56 . Although the mechanisms that regulate DMe development and signaling in gyrencephalic mammals remain unknown, in the developing human neocortex, expression of Wnt receptor FZD8 is higher than in the mouse and even the chimpanzee, potentially making the developing human neocortex particularly sensitive to dynamics of Wnt signaling 57 .…”
Section: Discussionmentioning
confidence: 99%
“…In mice, this pathway operates to prevent differential expansion of cortical progenitors and suppress gyrification of the distant neocortex. It has been recently demonstrated that similar to the mouse, a Wnt3a-expressing signaling center is also present in the DMe of the naturally gyrencephalic ferret 56 . Although the mechanisms that regulate DMe development and signaling in gyrencephalic mammals remain unknown, in the developing human neocortex, expression of Wnt receptor FZD8 is higher than in the mouse and even the chimpanzee, potentially making the developing human neocortex particularly sensitive to dynamics of Wnt signaling 57 .…”
Section: Discussionmentioning
confidence: 99%
“…However, these molecules have dispersion ranges maxing at a few hundred microns (Parchure et al., 2018). A recent study of these patterning mechanisms in the developing ferret cortex found that FGF and Wnt gradients and patterning centers were recapitulated (Jones et al., 2019). Importantly, the length of the developing neocortex along the anterior–posterior axis at the time of FGF‐induced patterning was comparable between ferrets and mice of equivalent developmental stages (Jones et al., 2019).…”
Section: Cortical Development As Told By Model Systemsmentioning
confidence: 99%
“…A recent study of these patterning mechanisms in the developing ferret cortex found that FGF and Wnt gradients and patterning centers were recapitulated (Jones et al., 2019). Importantly, the length of the developing neocortex along the anterior–posterior axis at the time of FGF‐induced patterning was comparable between ferrets and mice of equivalent developmental stages (Jones et al., 2019). However, ferret cortical expansion accelerated after these initial patterning stages (Jones et al., 2019).…”
Section: Cortical Development As Told By Model Systemsmentioning
confidence: 99%
See 2 more Smart Citations